Peripheral corneal thickness and associated factors – results from the population‐based German Gutenberg Health Study. Issue 6 (10th November 2021) - Fieß, Achim; Marx‐Groß, Susanne; Wasielica‐Poslednik, Joanna; Nagler, Markus; Schmidtmann, Irene; Wild, Philipp S.; Münzel, Thomas; Beutel, Manfred E.; Lackner, Karl J.; Pfeiffer, Norbert; Schuster, Alexander K.
Abstract: Purpose: Changes in peripheral corneal thickness are described in various corneal diseases such as corneal ectasia. However, few data exist describing the increase in corneal thickness from central to peripheral and reporting the normal distribution of corneal thickness in rings around the corneal centre. The aim of this study was to report these cornea characteristics and investigate associated factors in a population‐based setting. Methods: The Gutenberg Health Study is a prospective, population‐based study examining participants in a 5‐year follow‐up (age range 40–80 years) using Scheimpflug imaging. Corneal thickness was assessed in each participant at the apex, as well as in the corneal centre (thinnest corneal thickness) and in rings with 2, 4, 6, 8 and 10 mm diameter around the corneal centre, and the increase in corneal thickness towards the periphery. The relationship between corneal thickness at these locations and possible associated factors was determined using linear regression models. For this purpose, general and ocular parameters were included. Results: A total of 9729 participants were included in the present analysis (4874 women, age 59.2 ± 10.8 years). Multivariable analysis showed a correlation between the increase in corneal thickness in the circles from 0 to 10 mm (diameter) and the following parameters: age (B = −0.24 µm per year, p < 0.001); body height (B = −0.04 µm, p = 0.005); smoking (B = −0.72 µm, p < 0.001); spherical equivalent (B = −0.70 µm per dioptre, p < 0.001); white‐to‐white distance (B = −0.75 µm/mm, p < 0.001); mean corneal radius (B = −3.61 µm/mm, p < 0.001); intraocular pressure (B = −0.12 µm/mmHg, p < 0.001); glaucoma (B = −1.94 µm, p < 0.001); and pseudophakia (B = 0.89 µm, p < 0.001). Conclusion: The results of the present study suggest that several general and ocular parameters are associated with peripheral corneal thickness. In the context of diagnosing glaucoma, a smaller increase in corneal thickness towards the periphery might be a new additional marker.